Improvement design for power window mechanism of cable type - Mohd Farhan, Mohd Pilus (2009)
Power windows system or electric windows is divided in two types. They are cable type power window system and scissor type power window system. The main function of the power windows is to raise and lower automobile windows by depressing a button or switch, as opposed to using a hand-turned crank handle. The system have five components which are the window, the frame and guide rails, the electric motors and the door frame. In the cable type, the electric motors that are provided consist of the motor and a cable driven track that raises and lowers the window. The motor assembly will need to be fastened to the door frame. These components were reviewed for differences in shape and construction prior to being assembled to the vehicles. There are difference specifications for different manufacturers. For this project, power window system of Proton Gen-2 car was chosen to be benchmarking. Then the parts that always failed will be defined. The parts will be redesign and the material will be changed. The current and new parts were design by using SOLIDWORK software in dimensional of Proton Gen-2 car power window system. By using FEA tools that is ALGOR software, the design was analyzed using constant force. Improvement of power window parts design was compared based on material used, analysis on Stress Von Mises and displacement, buying and repairing cost, and others. The new design that will give the lowest value of Stress Von Mises and displacement will be selected as the improvement part. The material that will be selected also deal with the value of stress and displacement. The important result is to improve power window parts in order to enhance the life time of the system and to give advantages to the car users such as reducing the maintenance cost.